Canonical Wnt Signaling Ameliorates Aging of Intestinal Stem Cells - Nalapareddy, Kodandaramireddy (Cell Rep, 2017)
Although intestinal homeostasis is maintained by intestinal stem cells (ISCs), regeneration is impaired upon aging. Here, we first uncover changes in intestinal architecture, cell number, and cell composition upon aging. Second, we identify a decline in the regenerative capacity of ISCs upon aging because of a decline in canonical Wnt signaling in ISCs. Changes in expression of Wnts are found in stem cells themselves and in their niche, including Paneth cells and mesenchyme. Third, reactivating canonical Wnt signaling enhances the function of both murine and human ISCs and, thus, ameliorates aging-associated phenotypes of ISCs in an organoid assay. Our data demonstrate a role for impaired Wnt signaling in physiological aging of ISCs and further identify potential therapeutic avenues to improve ISC regenerative potential upon aging.